We can solve the system of equations using substitution by solving one equation for one variable and substituting it into the other equation.
From the first equation, we have:
y = 2 + 3x
Next, we substitute this expression for y in the second equation:
4x - 3(2 + 3x) = -16
Simplifying the equation:
4x - 6 - 9x = -16
-5x - 6 = -16
Adding 6 to both sides:
-5x = -10
Dividing both sides by -5:
x = 2
Now, we substitute this value back into the first equation to find the value of y:
y = 2 + 3(2)
y = 2 + 6
y = 8
Thus, the solution to the system of equations is x = 2 and y = 8.
Solve the system of two equations using substitution
y=2+3x
4x-3y=-16
1 answer